Genome-wide identification, characterization and functional prediction of the SRS gene family in sesame (Sesamum indicum L.) - Farjana Afroz Susmi; Tasmina Islam Simi; Md Nahid Hasan; Md Abdur Rahim (Oil Crop Science, 2024)
Sesame (Sesamum indicum L.) is an ancient oilseed crop of the Pedaliaceae family with high oil content and potential health benefits. SHI RELATED SEQUENCE (SRS) proteins are the transcription factors (TFs) specific to plants that contain RING-like zinc finger domain and are associated with the regulation of several physiological and biochemical processes. They also play vital roles in plant growth and development such as root formation, leaf development, floral development, hormone biosynthesis, signal transduction, and biotic and abiotic stress responses. Nevertheless, the SRS gene family was not reported in sesame yet. In this study, identification, molecular characterization, phylogenetic relationship, cis-acting regulatory elements, protein-protein interaction, syntenic relationship, duplication events and expression pattern of SRS genes were analyzed in S. indicum. We identified total six SiSRS genes on seven different linkage groups in the S. indicum genome by comparing with the other species, including the model plant Arabidopsis thaliana. The SiSRS genes showed variation in their structure like 2–5 exons and 1–4 introns. Like other species, SiSRS proteins also contained ‘RING-like zinc finger’ and ‘LRP1’ domains. Then, the SiSRS genes were clustered into subclasses via phylogenetic analysis with proteins of S. indicum, A. thaliana, and some other plant species. The cis-acting regulatory elements analysis revealed that the promoter region of SiSRS4 (SIN_1011561) showed the highest 13 and 16 elements for light- and phytohormone-responses whereas, SiSRS1 (SIN_1015187) showed the highest 15 elements for stress-response. The ABREs, or ABA-responsive elements, were found in a maximum of 8 copies in the SiSRS3 (SIN 1009100). Moreover, the available RNA-seq based expression of SiSRS genes revealed variation in expression patterns between stress-treated and non-treated samples, especially in drought and salinity conditions in. S. indicum. Two SiSRS genes like SiSRS1 (SIN_1015187) and SiSRS5 (SIN_1021065), also exhibited variable expression patterns between control vs PEG-treated sesame root samples and three SiSRS genes, including SiSRS1 (SIN_1015187), SiSRS2 (SIN_1003328) and SiSRS5 (SIN_1021065) were responsive to salinity treatments. The present outcomes will encourage more research into the gene expression and functionality analysis of SiSRS genes in S. indicum and other related species.